1997
DOI: 10.1021/np970182j
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Polyynes of Devil's Club (Oplopanax horridus), a North American Native Medicinal Plant

Abstract: Two new (3 and 5), as well as three known (1, 2, and 4), polyynes were isolated from Devil's Club (Oplopanax horridus; Araliaceae), a medicinal plant of North America. The structures were established by 1H and 13C NMR. The absolute configurations of 2 and 5 were determined by application of Mosher's method. All the polyynes exhibited significant anti-Candida, antibacterial, and antimycobacterial activity, with an ability to kill Mycobacterium tuberculosis and isoniazid-resistant Mycobacterium avium at 10 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
5
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 21 publications
5
127
5
1
Order By: Relevance
“…The chloroform extract of aerial parts significantly inhibited the growth of resistant Gram-negative bacteria P. aeruginosa (MIC 7.8 μg mL -1 ). Falcarinol, linoleic acid and palmitic acid, the main compounds in the chloroform extract of the aerial parts, exert antimicrobial activity [26,27]. Unsaturated fatty acids such as linoleic acid inhibit bacterial fatty acid synthesis by blocking bacterial enoyl-acyl carrier protein reductase (FabI) which is essential for production of lipidcontaining components such as cell membranes [28].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The chloroform extract of aerial parts significantly inhibited the growth of resistant Gram-negative bacteria P. aeruginosa (MIC 7.8 μg mL -1 ). Falcarinol, linoleic acid and palmitic acid, the main compounds in the chloroform extract of the aerial parts, exert antimicrobial activity [26,27]. Unsaturated fatty acids such as linoleic acid inhibit bacterial fatty acid synthesis by blocking bacterial enoyl-acyl carrier protein reductase (FabI) which is essential for production of lipidcontaining components such as cell membranes [28].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Falcarindiol (4C) was the most active constituent assayed in Angelica pubescens, a Chinese traditional treatment for arthritis, inhibiting 5-lipoxygenase with an IC 50 of 0.4 μM [297]. The (3S,8S) and (3R,8S)-isomers of 4C were shown to have antimycobacterial activity and to be active against multi-drug resistant strains of S. aureus [298,299]. Acetoxy modifications found in the known Apiaceae acetate 25I and oplopandiol acetate (25H) from Oplopanax horridus increase selectivity towards Mycobacterium spp.. Falcarindiol ethers with furanocoumarins, named japoangelols A-D (25J-M), are novel structures with the potential for enhanced contact toxicity [300]; both polyacetylenes and furanocoumarins in Apiaceae species are known to cause dermatitis.…”
Section: New Natural Productsmentioning
confidence: 99%
“…Very few studies on the natural products of this plant have been reported. 4,5 A study has described the presence of antimycobacterial polyynes in a methanol extract. 4 A recent publication reported the presence of some bioactive constituents in the root bark extracts of O. horridus from Alaska.…”
Section: -3mentioning
confidence: 99%
“…4,5 A study has described the presence of antimycobacterial polyynes in a methanol extract. 4 A recent publication reported the presence of some bioactive constituents in the root bark extracts of O. horridus from Alaska. 5 Silica gel chromatography of the extracts resulted in the isolation of certain essential oil constituents, such as (E)-nerolidol, the major component, followed by spathulenol, oplopanone and α-cubebene in lesser amounts.…”
Section: -3mentioning
confidence: 99%